A systematic analysis of ultrastructural lesions in the Plasmodium coatneyi splenectomized rhesus macaque model of severe malaria. Issue 5 (September 2022) - Lombardini, Eric D.; Turner, Gareth D. H.; Brown, Arthur E.; Inamnuay, Laksanee; Kaewamatawong, Theerayuth; Sunyakumthorn, Piyanate; Ferguson, David J. P.
Plasmodium falciparum remains one of the world's deadliest diseases and with ongoing concerns of evolving drug resistance, there is a need for continued refinement of the Plasmodium coatneyi infection model in macaques to study severe malaria. As such, the systemic ultrastructural lesions associated with P. coatneyi infection in splenectomized rhesus macaques was evaluated in 6 animals. Autopsy samples from multiple areas of the central nervous system (CNS), kidneys, heart, liver, and lungs of all 6 animals were processed for electron microscopy. A systematic analysis of the ultrastructural changes associated with the plasmodium was undertaken by multiple pathologists to ensure consensus. All tissues exhibited marked sequestration of infected red blood cells comprised either of cytoadherence to endothelium or rosette formation, associated with variable degrees of host cell damage in a range of tissues that in severe cases resulted in necrosis. This is the first complete systemic evaluation of ultrastructural tissue lesions in P. coatneyi –infected rhesus macaques, and the findings have important implications evaluating of the use of this model for the study of severe malaria caused by P. falciparum in humans.